The writer's style: a rhetorical field guide - Butler, Paul, author; Utah State University Press, publisher (Colorado State University. Libraries, 2018)
Designed to help students learn to use style as a rhetorical tool for college writing, taking into account audience, purpose, context, and occasion, A style guide for a new generation but also a new generation of style guide.--Provided by publisher.
The writer's style: a rhetorical style handbook
An introduction to style -- What is style? -- Style as thinking outside the box -- Why style matters -- Pushing the envelope -- Style in sentences -- Generative rhetoric -- Style in essays, including imitation and digital rhetoric -- Correctness, clarity, and concision, and sentence-combining -- Cohesion, coherence, and emphasis -- Practicing style -- Epilogue.
Keywords: Language and languages -- Style -- Study and teaching (Higher); Rhetoric -- Study and teaching (Higher)